Utilitarianism and economic behavior : looking for benthamite traces (2011)
In spite of the use of a utilitarian language in Rational Choice Theory, economists do not acknowledge any link to this current of moral philosophy, and have made great efforts to rid economics from its legacy. In this document we aim at assessing these efforts retracing their history from Pareto to Samuelson in order to determine how close they came to their ideal of formulating a positive science rid of what they called any metaphysical traces.